Scrambled eggs super! - Seuss, Dr. (London Collins, 2017)
When it comes to scrambling eggs, Peter T. Hooper needs something super special for his super-dee-dooper dish! And only the most interesting and exciting eggs from around the world will do...
Yellow band
Keywords: Rhyme -- Food